Alternative combinations of determinants creating financial strategy. The case of Polish university spin-off companies - Kwiotkowska, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The aim of this paper is to demonstrate the existence of alternative sets of determinants creating financial strategy of university spin-off companies in Polish conditions. To develop these topics Qualitative Comparative Analysis (QCA), an inductive analytic technique relying on set theory, was adopted. In this study, fifty-three selected Polish university spin-off companies (USOs) were characterized. The paper makes reference to the entrepreneurial finance literature which identifies some factors that influence the process of obtaining funds for new technology-based firms, like USOs. These factors can influence the possibility of financing positively or negatively and, as indicated in the literature including the entrepreneurial figure, the nature of the project, the financial scenario, and the market characteristics. In the paper, for each of these, deep insights into their relation to finance were provided. The following questions were asked: what added value can be provided by so-called informed capital, that is, a supply of money by a subject capable of evaluating innovative processes and technological issues and supporting the entrepreneur in running the business? And what are the roles of the two main types of capital sources, debt and equity, in the Polish context? What is important, therefore, “Do firms, especially small, young firms, get enough money to fund viable projects? And if not, what, if anything, should be done about it?” These questions are beguilingly simple to ask, and, needless to say, much less easy for economists to answer. The focus of this paper is, therefore, the analysis of the variables that determine the access to capital by USOs. This problem is highly relevant as Poland suffers from a significant delay in financial maturity compared to the United Kingdom and the United States, as well as to its closer nations, like France and Germany. The objective of this paper is to demonstrate the existence of alternative sets of determinants, creating the financial strategy of USOs. The study of the configuration of attributes was carried out using Boolean algebra − a notation system enabling the algebraic processing of logic statements. This analysis identified four alternative causal combinations associated with the entrepreneurial figure, the nature of the project, the presence of particular financial constraints and guarantees, and the market characteristics; one of them leads to VC funding, the next alternative two to debt financed by banks, and the last ones to government grants financing outcomes
Argumenta Oeconomica, 2020, Nr 1 (44), s. 387-412